2006
DOI: 10.1248/cpb.54.325
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-HIV-1 and Anti-HCMV Activity of 1-Substituted 3-(3,5-Dimethylbenzyl)uracil Derivatives

Abstract: 3-(3,5-Dimethylbenzyl)uracil (3) was treated with alkyl halides in the presence of alkali to give 1-substituted congeners. Condensation of 3 with alcohols using the Mitsunobu reaction was also employed as an alternative method. The anti-HIV-1 activity of 1-substituted analogues of 3-(3,5-dimethylbenzyl)uracil was evaluated according to previously established procedures. It appeared that the nitrogen of the 1-cyanomethyl group is important for anti-HIV-1 activity, suggesting interaction with the amino acid resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…These aryl substituted uracils were shown to block HIV-1 and HCMV replication in vitro in sub-micromolar concentrations. 31,32 Potent activity was also noted for a similar 1,3-dibenzyl inhibitor developed by Nair et al, which exhibited potent activity against the HIV integrase (Fig. 3).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…These aryl substituted uracils were shown to block HIV-1 and HCMV replication in vitro in sub-micromolar concentrations. 31,32 Potent activity was also noted for a similar 1,3-dibenzyl inhibitor developed by Nair et al, which exhibited potent activity against the HIV integrase (Fig. 3).…”
Section: Introductionsupporting
confidence: 62%
“…Additional examples pertinent to our approach can be found in the 1,3-dibenzyl-derivatives of uracil from Maruyama et al 31,32 (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…This is explainable, since the 6-azido uracil derivative (AzBBU) may be reduced metabolically to its 6-amino congener (AmBBU) in cell cultures (28). These compounds showed higher activity against III B than the 1-substituted 3-(3,5-dimethylbenzyl)uracils previously reported (33). In contrast, AzBBU and AmBBU were not active against III B-R , although the lead compound BBF-29 had weak activity.…”
Section: Discussionmentioning
confidence: 86%
“…Most NNRTIs are engaged in the H-bond with the backbone of the residues Lys101 and/or Lys103 of RT (13,26,41). Previous docking studies suggested an H-bond between the amide of Lys101 and nitrogen of the cyanomethyl and picolyl group of 1-substituted 3-(3,5-dimethylbenzyl)uracils (33). In our previous study, we showed that 6-subtitutions on the uracil ring resulted in elevation of the anti-HIV-1 activity of the uracil derivatives (28).…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of six-membered heterocyclic compounds such as pyrimidine ring is very important because of the synthetic condition and pharmacological properties [6][7][8][9][10]. It is noteworthy that fused heterocyclic structures containing pyrimidine ring exhibited diverse biological activities such as antimicrobial [11,12], DNA cleavage [13], anti-inflammatory [14], antiviral [15], anti-HIV [16] and antitumor [17]. Benzofuran nucleus directly linked at C-2 to various substituted heterocyclic ring systems exhibited promising biological activity [18].…”
Section: Introductionmentioning
confidence: 99%